A PDZ protein GIPC3 positively modulates hedgehog signaling and melanoma growth - Patmanathan, Sathya Narayanan (2022)
The hedgehog (Hh) pathway is essential for animal development, but aberrant activation promotes cancer growth. In this study, we show that GIPC3, a PDZ domain-containing protein with putative adaptor protein function, positively modulates Hh target gene expression in normal fibroblasts and melanoma cells and supports melanoma tumor growth. Using overexpression and epistasis studies, we show that Gipc3 potentiates Hh transcriptional output and that it modulates GLI-dependent transcription independently of Sufu. Whereas we find that GIPC3 protein does not interact with Hh pathway components, Ingenuity Pathway Analyses of GIPC3-interacting proteins identified by coimmunoprecipitation and mass spectrometry show an association with cancer pathogenesis. Subsequent interrogation of The Cancer Genome Atlas and the Human Protein Atlas databases reveals GIPC3 upregulation in many cancers. Using expression screens in selected groups of GIPC3-upregulated cancers with reported Hh pathway activation, we find a significant positive correlation of GIPC3 expression with Hh pathway components GLI1, GLI2, and GPR161 in melanoma lines. Consistently, GIPC3 knockdown in melanoma lines significantly reduces GLI1 and GLI2 expression, cell viability, colony formation, and allograft tumor growth. Our findings highlight previously unidentified roles of GIPC3 in potentiating Hh response and melanoma tumorigenesis and suggest that GIPC3 modulation on Hh signaling may be targeted to reduce melanoma growth.